Insights into how development and life-history dynamics shape the evolution of venom - Joachim M. Surm; Yehu Moran (EvoDevo, 2021)
Abstract Venomous animals are a striking example of the convergent evolution of a complex trait. These animals have independently evolved an apparatus that synthesizes, stores, and secretes a mixture of toxic compounds to the target animal through the infliction of a wound. Among these distantly related animals, some can modulate and compartmentalize functionally distinct venoms related to predation and defense. A process to separate distinct venoms can occur within and across complex life cycles as well as more streamlined ontogenies, depending on their life-history requirements. Moreover, the morphological and cellular complexity of the venom apparatus likely facilitates the functional diversity of venom deployed within a given life stage. Intersexual variation of venoms has also evolved further contributing to the massive diversity of toxic compounds characterized in these animals. These changes in the biochemical phenotype of venom can directly affect the fitness of these animals, having important implications in their diet, behavior, and mating biology. In this review, we explore the current literature that is unraveling the temporal dynamics of the venom system that are required by these animals to meet their ecological functions. These recent findings have important consequences in understanding the evolution and development of a convergent complex trait and its organismal and ecological implications.